The Oklahoma Quail Hunter - Ralph J. Ellis (National Quail Symposium Proceedings, 2017)
A questionnaire study of 2,690 Oklahoma quail hunters revealed that the most common type of hunter is a married man, 21 to 40 years old, who hunts 5 to 6 hr per day and 10 days per season. He hunts mostly on private lands about 35 miles from home and often has difficulty obtaining access for hunting. He is successful on ,0.75 of his hunting trips and harvests an average of 3.8 quail per trip. He spends about $9.60 per day while hunting. Saturday is his favored hunting day. Semiskilled workers earning about $7,000 per year are the most common type of hunter. The hunters are in agreement with the existing season, but many want 1 more day per week for shooting. Management implications of the findings are discussed.